Determinants of functional outcome after pediatric hemispherotomy - Ramantani, Georgia; Cserpan, Dorottya; Tisdall, Martin; Otte, Willem M.; Dorfmüller, Georg; Cross, J. Helen; van Schooneveld, Monique; van Eijsden, Pieter; Nees, Frauke; Reuner, Gitta; Krayenbühl, Niklaus T.; Zentner, Josef; et al. (Annals of neurology, 2024)
Objective We aimed to evaluate determinants of functional outcome after pediatric hemispherotomy in a large and recent multicenter cohort. Methods We retrospectively investigated the functional outcomes of 455 children who underwent hemispherotomy at 5 epilepsy centers in 2000-2016. We identified determinants of unaided walking, voluntary grasping with the hemiplegic hand, and speaking through Bayesian multivariable regression modeling using missing data imputation. Results Seventy-five percent of children were seizure-free, and 44% stopped antiseizure medication at a 5.1-year mean follow-up (range = 1-17.1). Seventy-seven percent of children could walk unaided, 8% could grasp voluntarily, and 68% could speak at the last follow-up. Children were unlikely to walk when they had contralateral magnetic resonance imaging (MRI) abnormalities (40/73, p = 0.04), recurrent seizures following hemispherotomy (62/109, p = 0.04), and moderately (50/61, p = 0.03) or severely impaired (127/199, p = 0.001) postsurgical intellectual functioning, but were likely to walk when they were older at outcome determination (p = 0.01). Children were unlikely to grasp voluntarily with the hand contralateral to surgery when they had Rasmussen encephalitis (0/61, p = 0.001) or Sturge-Weber syndrome (0/32, p = 0.007). Children were unlikely to speak when they had contralateral MRI abnormalities (30/69, p = 0.002) and longer epilepsy duration (p = 0.01), but likely to speak when they had Sturge-Weber syndrome (29/35, p = 0.01), were older at surgery (p = 0.04), and were older at outcome determination (p < 0.001). Interpretation Etiology and bilaterality of structural brain abnormalities were key determinants of functional outcome after hemispherotomy. Longer epilepsy duration affected language outcomes. Not surprisingly, walking and talking ability increased with older age at outcome evaluation. ANN NEUROL 2024;95:377-387
Online veröffentlicht: 14. November 2023
Gesehen am 29.01.2024